High-Tech and Tactile: Cognitive Enrichment for Zoo-Housed Gorillas - Clark, Fay E.; Gray, Stuart I.; Bennett, Peter; Mason, Lucy J.; Burgess, Katy V. (Frontiers in Psychology, 2019)
The field of environmental enrichment for zoo animals, particularly great apes, has been revived by technological advancements such as touchscreen interfaces and motion sensors. However, direct animal-computer interaction (ACI) is impractical or undesirable for many zoos. We developed a modular cuboid puzzle maze for the troop of six Western lowland gorillas (Gorilla gorilla gorilla) at Bristol Zoo Gardens, UK. The gorillas could use their fingers or tools to interact with interconnected modules and remove food rewards. 12 modules could be interchanged within the frame to create novel iterations with every trial. We took a screen-free approach to enrichment: substituting ACI for tactile, physically complex device components, in addition to hidden automatic sensors and cameras to log device use. The current study evaluated the gorillas’ behavioral responses to the device, and evaluated it as a form of ‘cognitive enrichment’. Five out of six gorillas used the device, during monthly trials of 1 hour duration, over a six month period. All users were female including two infants, and there were significant individual differences in duration of device use. The successful extraction of food rewards was only performed by the three tool-using gorillas. Device use did not diminish over time, and gorillas took turns to use the device alone or as one mother-infant dyad. Our results suggest that the device was a form of cognitive enrichment for the study troop because it allowed gorillas to solve novel challenges, and device use was not associated with behavioral indicators of stress or frustration. However, device exposure had no significant effects on gorilla activity budgets. The device has the potential to be a sustainable enrichment method in the long-term, tailored to individual gorilla skill levels and motivations. Our study represents a technological advancement for gorilla enrichment, an area which had been particularly overlooked until now. We wholly encourage the continued development of this physical maze system for other great apes under human care, with or without computer logging technology.